Efektifitas Rebusan Kurma Terhadap Peningkatan Hemoglobin Pada Remaja Anemia - Juleha Duwi Handayani; Sri Kustiyati (Jurnal Medika Nusantara, 2023)
Background; Anemia is a global problem that affects the health of women of childbearing age, One of the indicators of malnutrition such as stunting and wasting as well as decreased achievement in school, one way to treat anemia is by giving dates as an alternative. Dates contain iron, flavonoids, tannins, vitamins, and minerals which function as the synthesis and formation of hemoglobin. Objective; to determine the effect of rainwater-boiled dates on the increase in hemoglobin in adolescents MA AlIhsan who experience anemia. Method; This study was pre-experimental with a one-group pretest post-test design, The research sample used purposive sampling, the number of samples was 21 people, and data were processed using the T-test. Results; The normality test using the Shapiro-Wilk test sig > 0.000 with the Paired Sample t-test significance test obtained P = 0.000 (P <0.000) meaning that date boiled water can effectively increase hemoglobin levels in adolescents who experience anemia. Conclusion; Giving dates boiled water is effective in increasing hemoglobin in anemic adolescents at MA ALIhsan, Boyolali.